The Effect of Accountability on Performance of National Water and Sewerage Corporation in Uganda - Abas Olwol, Jasper; Byamukama Mpora, Eliab; Newton Kayongo, Isaac; Tukundane, Benson (International Journal of Scientific Research and Management (IJSRM), 2022)
The paper confirms that the effect of accountability on performance of national water and sewerage corporation in Uganda. Accountability can increase performance of an organization through implementing mechanisms which improve performance of individuals in those organizations. Such mechanisms include performance appraisals and specification of duties and responsibilities for each individual employee. The study was guided by objective to examine the effect of accountability on performance of national water and sewerage corporation in Uganda.The study adopted a descriptive correlational and cross-sectional survey design, involving mainly a quantitative approach and supplemented with a qualitative approach. The model is statistically significant, implying that all the three constructs of accountability taken together significantly affect performance of NWSC (F=64.119, sig. = 0.000). These results imply that, there are many other factors which influence performance of NWSC, other than accountability. According to the findings of this study, components like transparency significantly improve performance of an organization. In order to improve accountability and eventually the performance of the entire organization, management should put more emphasis on implementation of the control environment component of internal controls.